2018 44th Euromicro Conference on Software Engineering and Advanced Applications (SEAA) 2018
DOI: 10.1109/seaa.2018.00080
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Mapping Study on Security in Agile Requirements Engineering

Abstract: Background] The rapidly changing business environments in which many companies operate is challenging traditional Requirements Engineering (RE) approaches. This gave rise to agile approaches for RE. Security, at the same time, is an essential non-functional requirement that still tends to be difficult to address in agile development contexts. Given the fuzzy notion of "agile" in context of RE and the difficulties of appropriately handling security requirements, the overall understanding of how to handle securi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…Table 1 presents these studies in chronological order. However, most of these secondary studies (except the studies performed by Alsaqaf et al [10] and Villamizar et al [22]) have primarily reported on functional requirements, and QRs are only a marginal topic in their primary studies (see the third column in Table 1. In addition, the search strategies of existing secondary studies are not targeted at studies on QRs.…”
Section: Related Secondary Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 presents these studies in chronological order. However, most of these secondary studies (except the studies performed by Alsaqaf et al [10] and Villamizar et al [22]) have primarily reported on functional requirements, and QRs are only a marginal topic in their primary studies (see the third column in Table 1. In addition, the search strategies of existing secondary studies are not targeted at studies on QRs.…”
Section: Related Secondary Studiesmentioning
confidence: 99%
“…Except Alsaqaf et al [10] and Villamizar et al [22], existing secondary studies only superficially discuss QRs, or do not discuss them at all. Some highlight the limitations of agile methods when managing QRs and the risks of neglecting QRs [11,[16][17][18]21], and some identify strategies for managing QRs in ASD, such as the AFFINE framework, NORMAP, and SENoR [11].…”
Section: Related Secondary Studiesmentioning
confidence: 99%
See 3 more Smart Citations